Capital, non-capital and transformative politics in contemporary India - Deepankar Basu (University of Massachusetts, Department of Economics, 2019)
Kalyal Sanayal's work on postcolonial capitalism has been influential in many strands of critical social theory. In this brief note, I investigate three key components of his argument and find them wanting. In particular, I show that the evolution of land ownership in India does not support the claim that the primitive accumulation of capital is one of the important processes in operation in contemporary India. On the contrary, the evidence suggests that the process of primitive accumulation has been arrested or significantly slowed down. In addition to the critical comments on Sanyal (2007), I indicate towards an alternative framework that is better able to explain the key features of contemporary India.
Keywords: B24; O290; 330; postcolonial capitalism